2021
DOI: 10.1097/brs.0000000000004175
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia, Ectopic Fat Infiltration Into the Lumbar Paravertebral Muscles, and Lumbo-Pelvic Deformity in Older Adults Undergoing Lumbar Surgery

Abstract: The volume loss of skeletal muscle, including lumbar paravertebral muscles, is negatively correlated with the rate of lumbo-pelvic deformity. Moreover, ectopic fat infiltration with highly expressed adipogenesis promoting genes in the paravertebral muscles may reflect pathology of sarcopenia and may cause age-related lumbo-pelvic deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the elderly, paravertebral adipose tissue accumulates again due to ectopic fat infiltration into the lumbar paravertebral muscles. Its accumulation can also be observed in some pathological conditions with paravertebral muscle atrophy and degeneration [ 12 , 13 ]. In paediatric neurosurgery, treatment of tethered cord syndrome requires exposure of the spinal laminae before entering the spinal canal, opening the dura, and transecting the filum terminale that connects the spinal cord to the sacral bone [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, paravertebral adipose tissue accumulates again due to ectopic fat infiltration into the lumbar paravertebral muscles. Its accumulation can also be observed in some pathological conditions with paravertebral muscle atrophy and degeneration [ 12 , 13 ]. In paediatric neurosurgery, treatment of tethered cord syndrome requires exposure of the spinal laminae before entering the spinal canal, opening the dura, and transecting the filum terminale that connects the spinal cord to the sacral bone [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the severe FI group had a trend toward lower CL pre- and postoperatively. Evidence from the lumbar spine has also established the link between lumbar lordosis and FI ( 4 , 32 ). A biomechanical study by Patwardhan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the severe FI group had a trend toward lower CL pre-and postoperatively. Evidence from the lumbar spine has also established the link between lumbar lordosis and FI (4,32). A biomechanical study by Patwardhan et al (33) investigated kinematic, kinetic, and muscular responses to cervical sagittal imbalance, presenting increased SVA to be associated with shortening of the cervical flexor and lengthening of the cervical extensor.…”
Section: Fsua Of Fusion Level (°)mentioning
confidence: 99%
“…Why was pelvis flexion ROM also involved in the present regression model? Again, only LuM MFI (not fibrosis) would explain the positive relationship with ECHO LuM , as an increased MFI in the posterior vertebral muscles (erector spinae + LuM) has been associated with pelvic retroversion (Elysee et al, 2021; Lee et al, 2022; Zhang et al, 2021). However, MFI in LuM was not enough to induce a change in pelvic inclination in 93 healthy controls (Menezes‐Reis et al, 2018), which was later confirmed in a study showing a relationship with the erector spinae MFI but not LuM MFI in participants with spinal deformity (Miura et al, 2021).…”
Section: Discussionmentioning
confidence: 99%